Optimalisasi Edukasi Agensi Asik Creative dalam Affiliate Marketing untuk Daya Saing UMKM Digital - Resinando, Alberta; Khoirotunnisa, Fani (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
In the digital era, UMKM in Indonesia face major challenges in increasing their competitiveness due to low digital literacy and limited resources. Affiliate marketing is a potential solution to expand the market without large costs through collaboration with affiliate partners. The community service program carried out by Asik Creative Agency aims to improve UMKM digital literacy through affiliate marketing training. The methods used include a participatory approach with planning, implementation, observation, and reflection stages. The training includes theory and direct practice, such as recruiting affiliate partners, creating promotional content, and monitoring performance. The results showed an increase in participants' understanding of affiliate marketing by 85%, as well as the ability of UMKM to run digital marketing campaigns independently. Several participants reported an increase in customer visits of up to 40% in two months. Despite facing obstacles such as diverse internet access and digital literacy, this program has succeeded in providing real solutions in empowering UMKM. This program is expected to be a model of digital empowerment that can be replicated in other regions, while supporting Indonesia's digital ecosystem.